Formation of an algorithm for determining the criteria for the occurrence of critical events in gas condensate wells - Zarikovskaya, N; Piskarev, A; Kalyuzhny, E; Shpakovsky, G (Journal of physics. Conference series, 2020)
This work is devoted to the construction of an algorithm to identify criteria for the occurrence of critical events for gas condensate wells. In the course of the work, a sufficient amount of data obtained from telemetric sensors with a time interval of two years was analyzed. Among the data presented, critical events were recorded that formed the basis for the formation of the algorithm and criteria for identifying critical events. The data on parameter changes during hydrate formation, self-injection of the formation with water, and unstable well operation are presented. As a result of the work, criteria were identified on the basis of which general rules (algorithm) were formulated to identify critical events.